Implementasi Algoritme Enkripsi Grain-Cipher di ESP32 untuk Pengiriman Data lewat Modul Bluetooth Low Energy(BLE) - Muhammad Fawwaz Afif (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Grain-cipher Algorithm is a bit-oriented synchronous stream cipher. Grain-cipher is based on two shift registers, a linear feedback register, and Non-linear feedback register. The shift register has a size of 80 bits for key, and 64 bits for IV. Grain-cipher algorithm are chosen as the core of this research because of its lightweightness, which means that on its operation(encryption and decryption process), the algorithm will only uses a small amount of computing power. This research aims to see whether the algorithm will perform as it should in a constrained hardware environment. Grain-cipher are gonna do encryption and decryption process on ESP32 microcontroller. Bluetooth Low Energy(BLE) is going to handle the data transfer for both microcontrollers. In testing, the Grain-cipher algorithm performs the encryption and decryption method on the microcontroller without any problems. Result shows that ESP32 did both encryption and decryption process without any problems, and the data transfer between microcontroller using BLE, also performs very well. Exchanged data between the two microcontrollers is also cannot be read by the third microcontroller that doesn't have the key needed to do so(It will only show the ciphertext).